Analisis Komparasi Kinerja Laporan Keuangan Sektor Perbankan Menggunakan Metode RGEC : Studi Pada Bank Umum Indonesia, Malaysia Dan Singapura - YUSWANTO NUGROHO, ARIEF; FITRI MARDIANA, LELY (STIEKOP MALANG PRESS, 2024)
This study was conducted to analyze and compare the financial performance of banking from one country to another in ASEAN using the RGEC method, specifically in Indonesia, Malaysia, and Singapore, which are compared one by one to find out whether the two countries have significant differences or not. The selection of samples was made according to the large number of assets owned by ASEAN. The analysis was carried out by taking three banks from 2020-2023 representing each country so that the total sampling was 27 samples. The research hypothesis was tested using the normality test and the difference test (independent sample t-test). The results of the study showed that overall the banking of the three ASEAN countries had significant differences in the five ratio indicators. It can be seen from the sig (2-tailed) value on the NPL, LDR, ROA, NIM, and CAR indicators, which were less than 0.05.